ANALISIS KOMPETENSI KEWIRAUSAHAAN, ORIENTASI KEWIRAUSAHAAN, DAN KINERJA INDUSTRI MEBEL - ISA, Muzakar (Benefit, 2011)
The study aims to analyze the influence of competency aspects of entrepreneurship, entrepreneurial orientation on the performance of the furniture industry in Klaten, and analyze the impact of entrepreneurship on performance orientation furniture industry in Klaten. The data used are the primary data, taken in cross section through direct interviews with the owners of the furniture business by using a list of questions. The Sample is 182 funiture businesses or 10% of the population. Testing the validity of using Confirmatory Factor Analysis analyzes (CFA), and reliability testing using Cronbach Alpha. Analysis tool used hierarchical regression analysis. Based on the analysis concluded that (1) model 1 is the best model to explain the relationship between entrepreneurial competencies (skills), and entrepreneurship orientation on the performance of SMEs, (2) entrepreneurial competence (Initiative and enterprises, Planninng and Organizing, technology) as well as influential entrepreneurial orientation has positive and significant impact on performance, and (3) entrepreneurship orientation variable proved to mediate the relationship between entrepreneurial competencies and business performance in Klaten furniture.